The Influence of Promotion Intensity, Lifestyle, and Ease of Access on Online Loan Purchase Decisions among the Community in Pondok Benda Subdistrict, South Tangerang City - Nugraha, Adela Abdurachman; Soebadio, Bizzma Buana Amriki; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to evaluate the influence of promotional intensity, lifestyle, and ease of access on online loan purchase decisions among residents of Pondok Benda Village, South Tangerang City. Online loans have become a popular financing alternative due to their fast process, easy requirements, and high accessibility. The research method used a quantitative approach with a survey technique involving 100 respondents selected using purposive sampling. The data collection instrument was a questionnaire measuring promotional intensity, lifestyle, ease of access, and purchase decisions. Data analysis was conducted using multiple linear regression to test the effect of each independent variable on the dependent variable. The results indicate that promotional intensity, lifestyle, and ease of access, both partially and simultaneously, have a positive and significant influence on online loan purchase decisions. These findings suggest that marketing strategies, urban consumption patterns, and technological convenience are key drivers in the decision to use online loan services. Based on these results, it is recommended that fintech service providers pay attention to consumer education and promotional ethics to create a healthy and sustainable digital financial ecosystem.